Resection of the duodenum causes long-term endocrine and exocrine dysfunction after Whipple procedure for benign tumors - Results of a systematic review and meta-analysis. Issue 6 (June 2020) - Beger, Hans G.; Mayer, Benjamin; Poch, Bertram
Abstract: Background: Metabolic dysfunctions after pancreatoduodenectomy (PD) need to be considered when pancreatic head resection is likely to lead to long-term survival. Methods: Medline, Embase and Cochrane Library were searched for studies reporting measured data of metabolic function after PD and duodenum-sparing total pancreatic head resection (DPPHR). Data from 23 cohort studies comprising 1019 patients were eligible; 594 and 910 patients were involved in systematic review and meta-analysis, respectively. Results: The cumulative incidence of postoperative new onset of diabetes mellitus (pNODM) after PD for benign tumors was 46 of 321 patients (14%) measured after follow-up of in mean 36 months postoperatively. New onset of postoperative exocrine insufficiency (PEI) was exhibited by 91 of 209 patients (44%) after PD for benign tumors measured in mean 23 months postoperatively. The meta-analysis indicated pNODM after PD for benign tumor in 32 of 208 patients (15%) and in 10 of 178 patients (6%) after DPPHR (p = 0.007; OR 3.01; (95%CI:1.39–6.49)). PEI was exhibited by 80 of 178 patients (45%) after PD and by 6 of 88 patients (7%) after DPPHR (p < 0.001). GI hormones measured in 194 patients revealed postoperatively a significant impairment of integrated responses of gastrin, motilin, insulin, secretin, PP and GIP (p < 0.050-0.001) after PD. Fasting and stimulated levels of GLP-1 and glucagon levels displayed a significant increase (p < 0.020/p < 0.030). Following DPPHR, responses of gastrin, motilin, secretin and CCK displayed no change compared to preoperative levels. Conclusions: After PD, duodenectomy, rather than pancreatic head resection is the main cause for long-term persisting, postoperative new onset of DM and PEI.